Effects of polysaccharide isolated from Streptococcus thermophilus CRL1190 on human gastric epithelial cells - Marcial, Guillermo Emilio (2013)
EPS1190 was isolated from skim milk fermented with Stretococcus thermophilus CRL1190. The polysaccha-ride consisted of 33% glucose and 66% galactose with 1,4- and 1,4,6-galactose residues as main buildingblocks beside a high amount of 1,4-linked glucose. The polymer was characterized additionally con-cerning viscosity and zeta potential. EPS1190 stimulated cellular vitality and proliferation of humanstomach AGS cells and human buccal KB cells significantly. EPS1190 stimulated phagocytosis rate ofmurine macrophages RAW264.7 significantly. NO-release or anti-inflammatory effects by inhibition ofLPS-induced NO release were not observed. Confocal laser scanning microscopy revealed that EPS1190 ispartially internalized into AGS cells via endosomes. The bioadhesive absorption of FITC-labeled EPS1190into the mucus layer on the apical side of the epithelium using histological tissue sections from humanstomach was observed. Specific interaction of EPS1190 with mucin can be excluded as shown by micro-viscosimetry studies. EPS1190 increased the adhesion of H. pylori to AGS cells, which resulted in increasedsecretion of proinflammatory cytokines TNFa, IL-6 and IL-8. Summarizing, EPS1190 seems to stimulateepithelial cell regeneration and immunological innate defense mechanisms, which again can rationalizedthe use of this polysaccharide as cytoprotective compound in probiotioc preparations.